Case Report of a Poorly Differentiated Adenocarcinoma of the Appendix - Fukata, Shinji; Ito, Tadashi; Shirai, Kazuhisa; Mukaiyama, Hiroo; Yamaguchi, Ryuzo; Narita, Michihiko (Nippon Shokaki Geka Gakkai zasshi, 2004)
A 63-year-old woman was refered to our clinic for the evaluation of a right hypogastric pain. Ultra-sonography and computed tomography examinations revealed a cystic mass in the appendix. A right hemi-colectomy with D3 lymph node dissection was performed. Histological examination revealed a poorly differen-tiated adenocarcinoma of the appendix. Eighteen months later, an oophorectomy was performed because of ametastasis to the right ovary. The patient has shown no further signs of recurrence or metastasis for 2 yearsand 9 months since the first operation.